Handbook of leadership theory and practice : an HBS centennial colloquium on advancing leadership - Nohria, Nitin, 1962-; Khurana, Rakesh, 1967- (Harvard Business Press, 2010)
"The Handbook of Leadership Theory and Practice is based on the Harvard Business School Centennial Colloquium "Leadership: Advancing an Intellectual Discipline" and edited by HBS professors Nitin Nohria and Rakesh Khurana, this volume brings together the most important scholars from fields as diverse as psychology, sociology, economics, and history to take stock of what we know about leadership and to set an agenda for future research. This comprehensive volume explores leadership along many dimensions, including the development of leadership as a discipline, the contingencies leadership research needs to address if it is to develop as a subject, the nurturing of individual leaders, and the most critical problems facing practicing leaders today."--BOOK JACKET.